A new species and taxonomical notes on some other Catocala Schrank, 1802 (Lepidoptera, Erebidae) from China - Saldaitis, Aidas; Pekarsky, Oleg; Borth, Robert J. (Zootaxa, 2017)
A new species, Catocala nilssoni, sp. n., from the Liaoning and Shandong Provinces of northeast China is described. The new species clearly differs in wing pattern and genitalia from any other Catocala species. DNA results for one specimen of the new species further confirms its morphological exclusivity. Actual Catocala danilovi (O. Bang-Haas, 1927) male genitalia is pictured for the first time and the taxonomical status of the related Catocala florianii Saldaitis & Ivinskis, 2008 is discussed.